King grass (Hybrid Pennisetum) silages – quality and digestibility. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2006)
King Grass (Pennisetum purperium) is a newly introduced pasture grass in Malaysia. The dry matter yield of this grass is very high but the quality of the forage is mostly dependent on its maturity stages and climatic conditions. The quality of this herbage is high and the crude protein can reach I0%. It is palatable during early stage due to low lignin content and high sugar contents. In order to maintain the quality of this grass, one of the methods is to preserve the grass into silage. In general, silage is fermented. high moisture forage to be fed to ruminants (e.g. cattle and goat). Most often silage is made from grass.